2012
DOI: 10.1152/ajpendo.00502.2011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of body cell mass at bedside in critically ill patients

Abstract: Critical illness affects body composition profoundly, especially body cell mass (BCM). BCM loss reflects lean tissue wasting and could be a nutritional marker in critically ill patients. However, BCM assessment with usual isotopic or tracer methods is impractical in intensive care units (ICUs). We aimed to modelize the BCM of critically ill patients using variables available at bedside. Fat-free mass (FFM), bone mineral (Mo), and extracellular water (ECW) of 49 critically ill patients were measured prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 47 publications
2
54
0
2
Order By: Relevance
“…Nutritional markers, such as body mass index (BMI), albuminemia or transferrin, are made unreliable in ICU practice because of systemic inflammation and fluid balance disturbances [11]. Moreover, estimation of body composition as fat-free mass (FFM) is subject to many variations caused by injury and stress conditions in the ICU [12,13]. Body cell mass (BCM), the metabolically active part of FFM, is reported to be more specifically correlated to changes in nutritional status [11,14-16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional markers, such as body mass index (BMI), albuminemia or transferrin, are made unreliable in ICU practice because of systemic inflammation and fluid balance disturbances [11]. Moreover, estimation of body composition as fat-free mass (FFM) is subject to many variations caused by injury and stress conditions in the ICU [12,13]. Body cell mass (BCM), the metabolically active part of FFM, is reported to be more specifically correlated to changes in nutritional status [11,14-16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a lower BCM/FFM ratio is associated with higher extracellular water/intracellular water (ECW/ICW) [17]. It has been suggested that assessing BCM, BCM/weight or BCM/FFM ratios could help to provide more valuable markers of nutritional status and may promote understanding of the metabolic consequences of energy deficit [11,12]. Because of fluid shifts and poor renal and intestinal function during critical illness, the isotope and tracer dilution methods used for BCM measurements are impractical in critically ill patients, at least in the first or second week after their admission [15,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…They derived intra- and extracellular water volumes from low- and high-frequency resistances measured by multi-frequency bioelectrical impedance analysis (BIA) of body compartments, before and after hemodialysis. Moreover, they estimated body cell mass (BCM) from BIA parameters and anthropometric variables, based on a recently developed regression equation specific for ICU patients [2]. The investigation aimed at evaluating the consistency and clinical relevance of the current model for BCM calculation in case of massive changes in the external fluid balance.…”
mentioning
confidence: 99%
“…BCM can be directly measured by isotope dilution methods (that is, 40  K), or estimated by predictive equations [2]. However, the gold standard methods based on radioactive tracer techniques are not amenable to routine use in the ICU.…”
mentioning
confidence: 99%
“…There have been several questionnaires, e.g., short nutritional assessment questionnaire (SNAQ), developed to record recent involuntary weight loss or to determine patients at risk for undernutrition (Wijnhoven et al 2012). Interestingly, one study recently showed a technique to derive body cell mass (as a marker of skeletal muscle mass) from anthropometric data and weight change (Savalle et al 2012). This technique was validated with dual-energy X-ray absorptiometry (DEXA) scanning, showed an error of less than 20 %, and was found to be useful in identifying undernutrition in critical care.…”
Section: Nutrition Screening For Ali Patientsmentioning
confidence: 99%